2020
DOI: 10.3390/inventions5030033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dimple Height on Turbulent Heat Transfer of Fin Array with Alternate Convex/Concave Dimples

Abstract: This study analyzes transient turbulent modeling of three-dimensional multiple dimpled fin array using large eddy simulation (LES). The Navier–Stokes equations as well as the energy equation were constructed by the finite volume method and then discretized to form algebraic equations, which were solved by semi-implicit method for pressure-linked equation (SIMPLE). The solutions of temperature and velocity were obtained by iterating computation until it converged within each step. This simulation places nine fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…After studying these organisms, many scholars found that non-smooth micro-surfaces can produce unexpected reductions in drag performance. Currently, three types of surface microstructures exist: the groove type [91], the concave type, and the convex hull type [92]. Sharks are a typical example of a creature with a grooved surface.…”
Section: Heat Transfer and Flow Characteristics Of Drag-reducing Nano...mentioning
confidence: 99%
“…After studying these organisms, many scholars found that non-smooth micro-surfaces can produce unexpected reductions in drag performance. Currently, three types of surface microstructures exist: the groove type [91], the concave type, and the convex hull type [92]. Sharks are a typical example of a creature with a grooved surface.…”
Section: Heat Transfer and Flow Characteristics Of Drag-reducing Nano...mentioning
confidence: 99%